PEMANFAATAN APLIKASI PRIMASI DI YPPSB DALAM PENYELENGGARAAN LAYANAN PENDIDIKAN BERBASIS DIGITAL - Mulyono, Mulyono; Bashori, Sugeng (MPI STAI Sangatta Kutai Timur, 2023)
The developments in the globalization era have made technological developments rapidly develop in all lines of human life. The technological developments are not only limited to the development of fission tools or hardware therapy but also in the form of software. The development of application technology in the world of education for orderly administration and the digitalization of educational administration is growing rapidly. One of them is YPPSB, which is developing an application for administrative services for teachers and employees called the PRIMA application. In 2022, YPPSB, through the business manager and support, published an application called PRIMA. With this application, YPPSB provides easy administrative services, especially for teachers and employees who are under the auspices of YPPSB. Based on this, researchers are interested in knowing how to use the administrative services of teachers and employees at YPPSB through the PRIMA application at YPPSB. The research was conducted using qualitative methods by collecting data from results, interviews, observation, and documentation. Furthermore, the data was analyzed using interactive analysis, namely by condensing data, presenting data, and ending with conclusions. The results of the study can convey that the use of the PRIMASI application service at YPPSB has been going well with the convenience of teachers and employees in reporting administration at school. Based on the results of this analysis, it can be concluded that administrative services through the PRIMA application are registration and data collection of teachers and employees, validating teacher data, payroll and payment of overtime allowances for teachers and employees, submission of proposals, and data collection and repair of assets. Everything automatically uses the PRIMA application held by the operator at YPPSB, although I still found various obstacles.